Impacts of grazing on species diversity among different plant communities on the Qinghai–Tibet Plateau - Ma, Yu-Qi; Wang, Chun-Jing; Chen, De-Chao; Deng, Dong-Zhou; Yan, Wu-Xian; Yang, Jing-Yu; Wan, Ji-Zhong (Frontiers in Environmental Science, 2025)
The Qinghai–Tibet Plateau is a region with rich biodiversity and fragile ecosystems, and its plant species diversity is greatly affected by grazing activities. In this study, we aimed to explore the impact of grazing on the diversity of different plant communities on the Qinghai–Tibet Plateau. To this end, we collected grazing and vegetation data for the period of 1982–2015; calculated the grazing, Shannon–Wiener diversity, inverse Simpson’s, and Pielou’s evenness indices along with species richness; and conducted correlation and regression analyses. The results show that the grazing index was positively correlated with the richness of grassland plant communities, and in particular, there were significant relationships between the variance and maximum value of the grazing data and plant species richness. However, no significant correlations were found between the grazing index and diversity indices in shrub land and desert plant communities. Moderate grazing promotes the renewal and growth of grassland vegetation and increases plant species diversity. Therefore, grazing management plans should be developed based on specific ecological environments to achieve sustainable ecosystem development and to protect species diversity.